Perbandingan Hukum Pidana Negara Singapura Dan Hukum Pidana Indonesia Mengenai Tindak Pidana Pembunuhan Berencana - Riqa Kurnia Sabilla; Aurellya Ramadhani Syainda Putri; Yudi Anugrah Pratama; Muhammad Akbar Dzakira; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2025)
Criminal law is a set of regulations aimed at preventing criminal acts by deterring individuals from committing offenses. In the field of comparative criminal law, the study of its object focuses on analyzing criminal law disciplines to gain a deeper understanding of investigative methods and legal procedures. One example of comparative criminal law can be seen in the study of premeditated murder offenses in Indonesia and Singapore, which share similarities and differences in their legal systems. This discussion focuses on two main aspects: the application of sanctions for premeditated murder based on Indonesian criminal law (Article 340 of the Criminal Code) and Singaporean criminal law (Penal Code Act 224), as well as an analysis of the similarities and differences in the systematic approach of both regulations.This research employs a normative juridical approach with a descriptive-analytical nature, relying on primary, secondary, and tertiary legal sources. In Singapore, premeditated murder is regulated under Section 300 of the Penal Code Act 224, which imposes the death penalty. Meanwhile, in Indonesia, premeditated murder is stipulated in Article 340 of the Criminal Code, which provides sanctions in the form of the death penalty, life imprisonment, or imprisonment for a maximum term of 20 years.In general, Indonesia and Singapore have distinct legal systems. However, regarding the regulation of premeditated murder, both countries share similarities in legal provisions, while differences exist in terms of legal subjects and the application of sanctions.